1989
DOI: 10.1111/j.1365-2141.1989.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal megakaryopoiesis in patients with myelodysplastic syndromes: analysis of cellular and humoral defects

Abstract: In 13 patients with myelodysplastic syndrome (MDS) mature and immature erythropoietic (CFU-E, BFU-E), granulopoietic (CFU-GM) and megakaryopoietic (CFU-Meg) colony formation from human bone marrow mononuclear cells was evaluated in a microagar culture system. All but three patients exhibited abnormal CFU-Meg. The defect of CFU-Meg paralleled the reduction of BFU-E, whereas CFU-GM number declined to a lesser extent. Not only the CFU-Meg number, but also the number of megakaryocytes (Mk) per colony was reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
15
0
4
Order By: Relevance
“…18,28 In addition, the number of megakaryocytes per colony was also reported to be reduced. 29 Consistent with these studies, two-thirds of the patients, group III in our study, showed reduced numbers of CFU-meg; most of them were small colonies. However, there were some patients with normal or increased numbers of CFU-meg (group II and I) and thrombocytopenia simultaneously, suggesting poor platelet production in spite of sufficient megakaryocytic progenitors.…”
Section: Discussionsupporting
confidence: 78%
“…18,28 In addition, the number of megakaryocytes per colony was also reported to be reduced. 29 Consistent with these studies, two-thirds of the patients, group III in our study, showed reduced numbers of CFU-meg; most of them were small colonies. However, there were some patients with normal or increased numbers of CFU-meg (group II and I) and thrombocytopenia simultaneously, suggesting poor platelet production in spite of sufficient megakaryocytic progenitors.…”
Section: Discussionsupporting
confidence: 78%
“…In RAEB-T, two patients (cases 8,9) showed no increase in colony growth at each higher concentration, while one patient (case 7) showed a significant increase at 100 ng/ml of G-CSF.…”
Section: Resultsmentioning
confidence: 99%
“…include ineffective hemopoiesis, 23 impaired responsiveness to Elevated TPO concentrations were found in eight out of 12 patients growth factor stimulation, 24 and inhibitory mechanisms with decreased megakaryopoiesis and in only one out of the eight mediated by microenvironmental conditions including tumor patients with normal or increased megakaryopoiesis.…”
Section: Discussionmentioning
confidence: 99%